Blistering barnacles! What language do multilinguals Swear in?! - Dewaele, Jean-Marc (Sociolinguistic Studies, 2004)
The present contribution focuses on the effects of language dominance / attrition, context of acquisition, age of onset of learning, frequency of general use of a language and sociodemographic variables on self-reported language choice for swearing. The analysis isbased on a database to which 1039 multilinguals contributed through a web based questionnaire. Results suggest that, according to the self-reports, swearing happens most frequently in the multilinguals’ dominant language. Mixed instruction, an early start in thelearning process, and frequent use of a language all contribute to the choice of that language for swearing. Sociodemographic variables were not found to have any effect. Frequency of language choice for swearing was found to be positively correlated with perceived emotional force of swearwords in that language. Quantitative results based on answers to close-ended questions corresponded to participants’ responses to open-ended questions.